2010
DOI: 10.1080/15428052.2010.494533
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Sensory Characteristics of Doughnuts Made WithTrans-Fat-Free Canola Shortening,Trans-Fat-Free Palm Shortening, andTrans-Fat Vegetable/Soybean Shortening

Abstract: Because of the adverse health effects associated with consuming trans-fats, foodservice companies continue to reduce/eliminate the amount of trans-fats used to prepare doughnuts and other foods. People eat doughnuts because they like the taste, however, meaning companies must reduce/eliminate trans-fats in a manner that has minimal impact on consumer preference. This study evaluated the sensory characteristics of doughnuts fried in three shorteningsone trans-fat and two trans-fat-free. Overall, the doughnuts p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Fried products contain a high percentage of fat; therefore, the flavor and likability of fried food depends upon consumer perception and is affected by the type of oil used and the length of time the oil has been heated or used for frying (Melton, Jafar, Sykes, & Trigiano, 1994). In a study by Bordi, Snyder, and Hessert (2010), the sensory characteristics of donuts fried in one trans-fat shortening and two trans-fat-free shortenings was conducted to assure that those fried in healthier shortenings presented similar characteristics to those fried in the trans-fat shortening. The results showed that the donuts prepared with trans-fat-free shortening were comparable to those containing trans-fat according to hedonic scale evaluations with nontrained judges.…”
Section: Introductionmentioning
confidence: 98%
“…Fried products contain a high percentage of fat; therefore, the flavor and likability of fried food depends upon consumer perception and is affected by the type of oil used and the length of time the oil has been heated or used for frying (Melton, Jafar, Sykes, & Trigiano, 1994). In a study by Bordi, Snyder, and Hessert (2010), the sensory characteristics of donuts fried in one trans-fat shortening and two trans-fat-free shortenings was conducted to assure that those fried in healthier shortenings presented similar characteristics to those fried in the trans-fat shortening. The results showed that the donuts prepared with trans-fat-free shortening were comparable to those containing trans-fat according to hedonic scale evaluations with nontrained judges.…”
Section: Introductionmentioning
confidence: 98%